TEKNIK PEMERIKSAAN COMPUTED TOMOGRAPHY SCANNING (CT-SCAN) THORAKS DENGAN KLINIS LIMFOMA DI INSTALASI RADIOLOGI RSUD ARIFIN ACHMAD - Luthfi Farhan Yusuf (Medical Imaging and Radiation Protection Research Journal, 2024)
At the Radiology installation of RSUD Arifin Achmad, a thoracic CT-scan examination with clinical indications of lymphoma reveals differences in the procedure compared to field practices. The theoretical approach involves a slice thickness of 5-10 mm and a contrast injection delay of 2 seconds. However, in the practice, a slice thickness of 10 mm is used, and the contrast injection has either a 0- second delay or no delay. The research conducted is qualitative with a case study approach, focusing on three radiographers at RSUD Arifin Achmad in Riau Province. Data collection methods include observation, interviews, and documentation. The gathered data is then analyzed to draw conclusions based on the obtained information. The research findings indicate that in the Radiology Installation of RSUD Arifin Achmad, the thoracic CT-scan technique for lymphoma cases involves a slice thickness of 10 mm and a contrast injection with either a 0-second delay or no delay. This choice is justified by the fact that manually injecting the contrast media alone produces results that effectively highlight any abnormalities.